If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 10x + -6 + -3x = 3 Reorder the terms: 2 + -6 + 10x + -3x = 3 Combine like terms: 2 + -6 = -4 -4 + 10x + -3x = 3 Combine like terms: 10x + -3x = 7x -4 + 7x = 3 Solving -4 + 7x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 7x = 3 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = 3 + 4 7x = 3 + 4 Combine like terms: 3 + 4 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 6-6(m-2)=3m | | Ft-9h=10j | | -5r-5r=10 | | 5(x+7)+4x=7(x-1) | | .50(x-800)+59.99=144.49 | | -ph-15=93 | | 15c-19c= | | -236=-4b+6(-5b+6) | | 22x-6-13x+2=25x-8-16x+15 | | 10x=-8x+10 | | -21a+28+-6=10.2 | | X+10=-(x-6) | | 2.5x+1.6=15.6 | | -236=-4b+6(-5bg+6) | | -2x-(-1)=5 | | 2(y-5)=3(y+2)-8 | | -216=8+8(4-8a) | | 12-4x=2x+6 | | 2n-5-30=-3(6+5n) | | 6t+2+3t+17=30 | | 0.60x+0.10(100-x)=120 | | 8.3p^2+4.8p^2= | | -4(r+3)=-43 | | x-20=57 | | d-6= | | -4-3(9z-3)= | | 10m+-5=67+m | | -3x-(-1)=10 | | 7x+12-9x=20-18x+16x-8 | | -2/5+n=-1/15 | | x+4=3fourth | | I=vw+z |